The Pérez Chacel couple and the magazine «Estaciones». A project in Brazilian exile. Two unpublished poems by Rosa Chacel (Castilla. Estudios de Literatura, 2022)
The magazine Estaciones was an unborn Brazilian project by the Pérez-Chacel couple in the first years of their exile, after the Civil War. The materials of the magazine, largely unpublished poems and letters, are preserved in the Timoteo Pérez Rubio Archive in the Extremaduran and Ibero-American Museum of Contemporary Art (MEIAC) in Badajoz. The interest of Estaciones lies not only in giving us a sample of the secret poetry of Timoteo Pérez Rubio or in confirming the importance of the figure of the Brazilian poet Vito Pentagna as a close friend of the Pérez-Chacel couple and Timoteo's patron in Brazil; but also in bequeathing us an unpublished version of a poem by Gil-Albert from the first years of his exile and, fundamentally, two unpublished ones by Rosa Chacel, linked to the writing cycle of her Versos prohibidos.
Keywords: poetry of exile; literary magazine; unpubunpublished poems of Rosa Chacel